2007
DOI: 10.1073/pnas.0702027104
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of the protein disulfide proteome by mitochondria in mammalian cells

Abstract: The majority of protein disulfides in cells is considered an important inert structural, rather than a dynamic regulatory, determinant of protein function. Here, we show that some disulfides in proteins also are regulated by cell redox status with functional consequences. We find that reactive oxygen species (ROS) produced by mitochondria are actively used by cells to facilitate cell-surface protein disulfide formation, as well as folding and transport, in mammalian cells. Inhibition of mitochondrial ROS produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
107
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 27 publications
2
107
0
Order By: Relevance
“…The Env folding involves cross-linking of 20 cysteine residues, which is dependent on heavy N-glycosylation and the most oxidizing redox status in the ER (31). It has been suggested that the oxidative protein folding in the ER is controlled by mitochondria, likely via regulating the ER redox status through releasing reactive oxygen species (32). Intracellular reactive oxygen species is mainly produced by mitochondria as a byproduct from energy production.…”
Section: Discussionmentioning
confidence: 99%
“…The Env folding involves cross-linking of 20 cysteine residues, which is dependent on heavy N-glycosylation and the most oxidizing redox status in the ER (31). It has been suggested that the oxidative protein folding in the ER is controlled by mitochondria, likely via regulating the ER redox status through releasing reactive oxygen species (32). Intracellular reactive oxygen species is mainly produced by mitochondria as a byproduct from energy production.…”
Section: Discussionmentioning
confidence: 99%
“…However, an emerging concept identifies two types of disulfide bonds, a structural group and a redox-sensitive regulatory group, with the latter having direct functional consequences for the cell [27,28]. After bacterial transcription factor OxyR was found to be directly activated by thiol oxidation [29], increasing numbers of reports have recently shown that covalent modification of cysteines by disulfide formation can activate proteins in mammalian cells [30][31][32] and that disulfides are rapidly formed on cell surfaces in response to changes in the cellular redox state [28]. In agreement with these novel concepts, our finding that oxidative modification of caspase-9 can promote its activation has provided a previously undescribed perspective of how oxidative stress induces apoptosis; in addition to the Figure 5 Cys403 mutation blunted the sensitivity of caspase-9 to H 2 O 2 -induced auto-cleavage and decreased the formation of disulfide-dependent complex and apoptosomes.…”
Section: Discussionmentioning
confidence: 99%
“…A method to label disulfides in cells is described in a recent report [9]. The protocol uses iodoacetamide to block free thiols, DTT to reduce disulfides and iodoacetamide-conjugated fluorescein as a probe.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, proteomic methods to identify disulfides in proteins have been established [6][7][8]. However, means to image exact loci of thiol oxidation in cells and tissues are quite limited [9]. Imaging techniques would be particularly useful, since the redox environment differs between cell types and even subcellularly.…”
mentioning
confidence: 99%
See 1 more Smart Citation